2018
DOI: 10.1186/s10033-018-0285-7
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis and Verification of the Gas Jet from Aircraft Engines Impacting a Jet Blast Deflector

Abstract: The process of the gas jet from aircraft engines impacting a jet blast deflector is not only a complex fluid-solid coupling problem that is not easy to compute, but also a safety issue that seriously interferes with flight deck environment. The computational fluid dynamics (CFD) method is used to simulate numerically the impact effect of gas jet from aircraft engines on a jet blast deflector by using the Reynolds-averaged Navier-Stokes (RANS) equations and turbulence models. First of all, during the pre-proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Gong et al [30] proposed an improved delay separation vortex simulation (IDDES) method based on the SST model for a high-precision simulation of the jet engine effect and conducted a numerical study of the dynamic jet effect through a RANS/ LES hybrid method. eir results showed that the velocity distribution in a jet blast can be predicted better [31,32].…”
Section: Introductionmentioning
confidence: 94%
“…Gong et al [30] proposed an improved delay separation vortex simulation (IDDES) method based on the SST model for a high-precision simulation of the jet engine effect and conducted a numerical study of the dynamic jet effect through a RANS/ LES hybrid method. eir results showed that the velocity distribution in a jet blast can be predicted better [31,32].…”
Section: Introductionmentioning
confidence: 94%